Maternal Recognition of Pregnancy in the Horse: Are MicroRNAs the Secret Messengers? - Smits, Katrien (Int J Mol Sci, 2020)
The signal for maternal recognition of pregnancy (MRP) has still not been identified in the horse. High-throughput molecular biology at the embryo–maternal interface has substantially contributed to the knowledge on pathways affected during MRP, but an integrated study in which proteomics, transcriptomics and miRNA expression can be linked directly is currently lacking. The aim of this study was to provide such analysis. Endometrial biopsies, uterine fluid, embryonic tissues, and yolk sac fluid were collected 13 days after ovulation during pregnant and control cycles from the same mares. Micro-RNA-Sequencing was performed on all collected samples, mRNA-Sequencing on the same tissue samples and mass spectrometry was conducted previously on the same fluid samples. Differential expression of miRNA, mRNA and proteins showed high conformity with literature and confirmed involvement in pregnancy establishment, embryo quality, steroid synthesis and prostaglandin regulation, but the link between differential miRNAs and their targets was limited and did not indicate the identity of an unequivocal signal for MRP in the horse. Differential expression at the embryo–maternal interface was prominent, highlighting a potential role of miRNAs in embryo–maternal communication during early pregnancy in the horse. These data provide a strong basis for future targeted studies.